Cryptography - Douglas R. Stinson (Chapman & Hall/CRC, 2006)
Offers coverage of the use of cryptographic protocols that establish the steps that must be taken before any type of secret transmission can be completed. This book shows readers how the various parties to the transaction establish their cryptographic identities or keys